RANCANG BANGUN APLIKASI PENDATAAN STATUS GIZI PADA BALITA BERBASIS WEB DI DESA RAWALELE - Sari Azhariyah; Usep Abdul Rosid; Taufan Abdurrachman; Wulan Siti Nurul Masriah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Nutritional status is a measure of nutritional status that affects human growth and development, so nutritional status data collection is necessary. Data on nutritional status in Rawalele Village was collected by village midwives, who were assisted by posyandu cadres in recording child weighing data and then submitting it to the puskesmas and entering it into the ePPGBM system. Due to difficulties with existing applications, data collection on nutritional status at the Rawalele village posyandu is still done on paper, so the process takes a long time and data can be lost or damaged. The purpose of this study is to design and build a web-based application to facilitate data collection on nutritional status in toddlers. A software model is obtained using the prototype development method. The prototype development method is used to create a software model, which aids in the development of a system that matches the facts of toddler growth and development data. The findings revealed that posyandu cadres could use the nutritional status data collection application for toddlers, making it easier for puskesmas to collect data from each posyandu.